Lymphoepithelial carcinoma of the maxillary sinus: A case report and review of the literature. Issue 28 (July 2018) - Takakura, Hiromasa; Tachino, Hirohiko; Fujisaka, Michiro; Nakajima, Takahiko; Yamagishi, Kentaro; Ishida, Masayuki; Shojaku, Hideo
Abstract: Rationale: Most cases of lymphoepithelial carcinoma (LEC) occur in the nasopharynx, and LEC in the sinonasal tract is extremely rare; thus, the clinical characteristics of sinonasal LEC are not well known. Patient concerns: A 63-year-old Japanese man presented with a three-week history of left cheek pain, nasal obstruction and cheek swelling. Diagnoses: Enhanced CT and MRI revealed a tumor of the left maxillary sinus that invaded the left orbit and hard palate, with multiple swollen left cervical lymph nodes. Open biopsy was performed, and the specimen was diagnosed as LEC. Interventions: Alternating chemoradiotherapy (ALCRT) followed by salvage surgery was performed. Outcomes: Our patient has been disease free for 5 years. Lessons: A literature review of the epidemiology, etiology, clinical course and management of sinonasal LEC is highlighted. We believe ALCRT followed by salvage surgery to be a highly optimal treatment for sinonasal LEC from the viewpoint of a balance between quality of life and a high curative effect.